Advantage in Reading Lexical Bundles is Reduced in Non-Native Speakers - Matteo Valsecchi; Viktoria Künstler; Sven Saage; Brian J. White; Joybrato Mukherjee; Karl R. Gegenfurtner (Bern Open Publishing, 2013)
Formulaic sequences such as idioms, collocations, and lexical bundles, which may be processed as holistic units, make up a large proportion of natural language. For language learners, however, formulaic patterns are a major barrier to achieving native like competence. The present study investigated the processing of lexical bundles by native speakers and less advanced non-native English speakers using corpus analysis for the identification of lexical bundles and eye-tracking to measure the reading times. The participants read sentences containing 4-grams and control phrases which were matched for sub-string frequency. The results for native speakers demonstrate a processing advantage for formulaic sequences over the matched control units. We do not find any processing advantage for non-native speakers which suggests that native like processing of lexical bundles comes only late in the acquisition process.